PEMBERIAN PUPUK KASCING DAN POC NASA PADA PERTUMBUHAN DAN PRODUKSI BAWANG MERAH (Allium ascalonicum L.) - Eni Farida; Saripah Ulpah; T. Edy Sabli (UIR Press, 2018)
ABSTRACT The purpose of this study was to determine the effect of applying vermicompost fertilizer and POC Nasa on the growth and production of shallots (Allium ascalonicum L.). This research has been carried out in the Experimental Garden of the Faculty of Agriculture, Riau Islamic University for 4 months, starting from July to October 2018. The design used in this study was a factorial Completely Randomized Design consisting of 2 factors. The first factor is vermicompost fertilizer (K) which consists of 4 levels namely 0, 200, 400, 600 g / plot and the second factor is POC Nasa (P) consisting of 4 levels namely 0, 2, 4, 6 cc / l water. The parameters observed in this study were plant height, harvest age, number of tubers per clump, wet tuber weight per sample, dry tuber weight per sample, tuber weight loss. The last observation data were statistically analyzed and continued with a BNJ follow-up test at the 5% level. The results showed that the application of vermicompost fertilizer and poc nasa interaction significantly affected the parameters of plant height, age of harvest, the number of tubers per clump, dry tuber weight per sample, shrinkage of tuber weight, and the application of vermicompost fertilizer and poc nasa interactively had no significant effect on wet tuber weight parameters per sample with the best treatment is a concentration of 600 g / plot (K3) and 6 cc / water (P3) is a dose of 44.80 grams/plot. Keywords: POC, Kascing, Shallot